Sobre caboclos e (in)visibilidades no Contestado : pacto de segurança, biopolítica e imagens-frame no documentário brasileiro de celebração centenária - Oliveira, Valéria Cristina de (2017)
This theses is based on Foucauldian theories which incorporate the Discourse Analysis of French line, in their Brazilian discussions and developments, aiming at looking the individual and their instant , instance of problematization of subject and discourse. This research comprises that biopolitics, inchmeal started between threshold of XIX century still under the monarchy order in Brazil and republican beginnings from XX century, it was the control procedure established, in State actions visibility, to act over civil movement, named the Contestado War. In this sense, the political and economic practice of biopower, from the past up to the present, as a governmentally strategy to end the conflict, enlisting the caboclo individual, discoursed as a Contestado rebel, into oblivion and reiteration of exclusion in discursive practices, which are investigated in the editing of photographs turned into ephemeral in documentaries. These material elements are characteristic to appear as a biopolitical practice of recollection/memory/celebration of centenarians and are converted, in this investigation, into corpus of research. Such conditions of possibility gave rise to "security pact" and established marginalisation and social deletion to the caboclos of Contestado . In that way, the negligence and abandonment created the emergence of discourse of recollection; senses that, in celebration of the centennial, are redefined and resumed in contemporary statements. From this scenario, we were exceptionally interested in the conditions of discourse emergency revealed by centennial celebrations of the event; the conditions of existence in expressed claim about the celebrated centennial; and the possibilities of iconographic experience organized in photography animation- put the stabilisation and use fields into operation that guarantee the unity and identity expressed in documentaries. Thus, Corpus Analysis is composed by: two documentary video productions, applying techniques of movement in photography, in which the topic is the factual and discursive Contestado War event − Meninos do Contestado (2012) and Olhar Contestado: desvendando códigos de um conflito (2012). Both documentaries invest in a discursive set essentially based on the story of the Contestado War, giving prominence to the iconographic materiality, which, under such texture, destabilizes the viability schemes and enunciation. So, the search object recalls memory, power, truth and biopolitics related to the technical knowledge of photographical material elements edits and discursive knowledge. All this knowledge together highlights legal power discourses, rather than others, which leads us to discuss: Does the possibility of visibility and visuality, in the image/frame, produce relations of expressed remanence, which moves and disperses the way of viewing and saying minority population, known as cabocla , in documentaries about Contestado War centennial? Therefore, our goal is to investigate how and why the photo animation, calling the recollection of Contestado War for its centennial celebrations, presents this historic and discursive event in audiovisual documentary, giving it a new texture, and for this model of scripture , gives visibility to governmentality by the technologies of biopower and biopolitics. As a result, this study has shown, in this discursive part, the set of technical knowledge and visibility of enunciation of video production, which shows aspects of an unwanted and abandoned community and of a memory that wants to be present. The images-frame mark, discursively, the existence of a break period in the security pact aiming at a killing and deleting State. The reading gestures undertaken by analytics, showed in these imagistic discursive material elements, the way that the material listed is settled, keeping the stabilization fields of senses caboclo individuals. Above all, it was presented how these animations are in other schemes of looking and saying in the cabocla population, in which reinstatement does not change the statements about Contestado , but place them in relation to other sayings, moving and forming current practises. The research shows that, included in other ways, such as the technological making documentaries, which animates them, the images-frame expose the imagistic and non-imagistic discourse and stablish an existent hybrid place for this iconographic enunciation and the support of knowledge and institutional order that they obey.